2021
DOI: 10.3390/brainsci11111453
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Perturbational Complexity in Cortical Cultures

Abstract: Dissociated cortical neurons in vitro display spontaneously synchronized, low-frequency firing patterns, which can resemble the slow wave oscillations characterizing sleep in vivo. Experiments in humans, rodents, and cortical slices have shown that awakening or the administration of activating neuromodulators decrease slow waves, while increasing the spatio-temporal complexity of responses to perturbations. In this study, we attempted to replicate those findings using in vitro cortical cultures coupled with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…On the other hand, in vitro studies on brain waves in 2D neuronal cell cultures may be limited by the difficulty of reproducing the properties of the underlying brain wave network and key differences may result comparing cultures of dissociated cortical neurons with in vivo models or with neurons cultured in vitro with more preserved architectures. 27 Indeed, 2D neuronal models are limited to side-by-side contact, lacking a 3D microenvironment and the relevant interactions between the cells and the surrounding extracellular matrix. However, pioneering studies carried out by the Tafti group 38 and by Colombi et al.…”
Section: In Vitro Entrainment Of Rhythms and Waves In 3d Cel...mentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, in vitro studies on brain waves in 2D neuronal cell cultures may be limited by the difficulty of reproducing the properties of the underlying brain wave network and key differences may result comparing cultures of dissociated cortical neurons with in vivo models or with neurons cultured in vitro with more preserved architectures. 27 Indeed, 2D neuronal models are limited to side-by-side contact, lacking a 3D microenvironment and the relevant interactions between the cells and the surrounding extracellular matrix. However, pioneering studies carried out by the Tafti group 38 and by Colombi et al.…”
Section: In Vitro Entrainment Of Rhythms and Waves In 3d Cel...mentioning
confidence: 99%
“…However, pioneering studies carried out by the Tafti group 38 and by Colombi et al. 12 , 27 on spontaneous and pharmacologically manipulated 2D neuronal culture activities, in terms of brain waves linked to the sleep/wake cycle, will be discussed in the following section. These authors claimed to artificially “drive” the connectivity of neurons within the cultured network, as cell cultures are not necessarily random networks, but their versatile neuronal growth can be manipulated to develop networks with different topologies, such as a 3D cytoarchitecture.…”
Section: In Vitro Entrainment Of Rhythms and Waves In 3d Cel...mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies in cortical slices, found that application of noradrenaline and a cholinergic agonist increased the PCI (D'Andola, Rebollo et al 2018), whereas GABA antagonists reduced PCI (Barbero-Castillo, Mateos-Aparicio et al 2021). In contrast, rat cortical cell cultures show only moderate effects of cholinergic agonists on PCI values presumably due to a lack of appropriate circuit architecture (Colombi, Nieus et al 2021). However it is unclear which circuit elements, e.g.…”
Section: Introductionmentioning
confidence: 99%